2020
DOI: 10.1186/s12913-020-05795-1
|View full text |Cite
|
Sign up to set email alerts
|

Health facility readiness and provider knowledge as correlates of adequate diagnosis and management of pre-eclampsia in Kinshasa, Democratic Republic of Congo

Abstract: Background Hypertensive disorders in pregnancy are the second most common cause of maternal mortality in the Democratic Republic of Congo (DRC), accounting for 23% of maternal deaths. This study aimed to assess facility readiness, and providers’ knowledge to prevent, diagnose, and treat pre-eclampsia. Methods A facility-based cross-sectional study was conducted in 30 primary health centres (PHCs) and 28 referral facilities (hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 51 publications
1
25
1
Order By: Relevance
“…Preeclampsia is the second most common cause of maternal mortality in the world responsible for 10-15% of maternal death. 3 It affects 3-5% of pregnant women worldwide and reported one of the main causes of maternal mortality, morbidity and still births. 4 The prevalence of complication with maternal and fetal outcome is 19% with pre-eclampsia in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preeclampsia is the second most common cause of maternal mortality in the world responsible for 10-15% of maternal death. 3 It affects 3-5% of pregnant women worldwide and reported one of the main causes of maternal mortality, morbidity and still births. 4 The prevalence of complication with maternal and fetal outcome is 19% with pre-eclampsia in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…5 According to recent ranking Pakistan is third in terms of burden of fetal, maternal and child mortality. 3 Our country has poorest pregnancy outcomes worldwide, maternal mortality was found to be 319 per 100,000 live births. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were also recorded in a study carried out in Northern Karnataka in India [14] that found out that majority of respondents had high knowledge on pre-eclampsia. Another study done in Kinshasa revealed that although all provider groups had significant knowledge gaps about pre-eclampsia, health providers in hospitals demonstrated slightly more knowledge compared to those in PHCs [15] . This finding is not surprising given that physicians are more plentiful in hospitals than in PHCs and they tend to be more knowledgeable than other health specialists.…”
Section: Discussionmentioning
confidence: 97%
“…Similar findings were discovered in a study that was done in Kinshasa which revealed poor availability of health commodities to manage pre-eclampsia, as half of facilities had a readiness score lower than 53.8% and no facility had all the nominated commodities at the time of the study. This poor availability was attributed to inconsistent supply chain as only a few facilities mainly hospitals and public facilities received these commodities from government or NGOs and as a result health facilities usually asked patients or their relatives to purchase drugs from outside pharmacies [15] . The implication of poor availability of drugs and supplies in the management of PE in health facilities is that there may be a lag of time till the drug is made available, depending on affordability and proximity to the pharmacies where they are purchased by patients and this delay may worsen the pregnancy outcome which can contribute to high maternal mortality deaths.…”
Section: Discussionmentioning
confidence: 99%